Leggere Istanbul Memoria e lingua nella narrativa turca contemporanea - MARAUCCI, TINA (Biblioteca di Studi di Filologia Moderna, 2020)
Using the metaphor of the city-text, the volume investigates in a comparative perspective the representations of Istanbul in the works of two pairs of authors: Ahmet Hamdi Tanpınar/Orhan Pamuk and Yaşar Kemal/Latife Tekin. The notions of memory and language provide the main hermeneutical cyphers in the analysis of each urban poetics, considered respectively as attempts of (re)writing and translation of mnesic and cultural text of the city in the literary space of high national culture. Moving from the centre to periphery, such an itinerary aims to highlight the intimate relationship between forms of aesthetical appropriation of urban space-time and (de)construction processes of Turkish national canon.